The Products of Turbulent Times: Continuities and Change of 17th Century Neutral Iroquoian Ceramic Technology - Ionico, Daniel A. (My University, 2019)
Archaeologists today increasingly consider the relationship between historical processes and the production practices of past potters. In this thesis, I utilize extant Neutral Iroquoian assemblages from Southern Ontario to explore continuities and discontinuities in ceramic production practices during a time of profound socio-demographic turbulence in the early 17th century A.D. The Neutrals contributed and responded to an increase in regional violence, migration, and cultural interaction that involved taking in refugees, escalating captive-taking raids against enemy nations, and intensifying regional trade-networks along European and indigenous routes, while also experiencing and responding to traumatic demographic losses produced by European-disease epidemics. I employ the relational and historical communities of practice approach to orient my perspectives on technical styles to the lived experiences of learning and production among Iroquoian potting communities. The distinct emergence of shell-tempered ceramics in the Spencer-Bronte Creek site cluster served as an anchor for my investigation on how Neutral potters renegotiated and articulated potting practices during times of turbulence. I examined pottery production practices at the chronologically sequential Christianson and Hamilton sites through a multi-attribute analysis, ceramic petrography, and oxidation analysis. In this comparative approach, I found the likely presence of more than one community of practice at each site, speaking to the possibility of migration events. I found that a significant degree of continuities in technical style and a slight decrease in skill can speak to an adaptability of ‘open learning’ production communities, where broader numbers of persons held technical knowledge as peripheral non-specialists and they could have taken up the craft during times of community member reconstitutions after epidemics. Through time, conditions of turbulence brought about a greater diversity of practices and styles among communities of production as indicated through an increased blending of alternative practices in local operational chains and a decrease in their regimentation. These alterations are likely produced through ‘micro-histories’ at play within the household production scales constituting each village.